PENGARUH GETARAN PADA MOTOR SAMPLING PUMP ROUGHER SCAVENGER TERHADAP KONSUMSI DAYA LISTRIK DI PT NEWMONT NUSA TENGGARA - Zainuri Achmad; Sujita Sujita; Yudistira Yudistira (JURNAL ILMIAH MOMENTUM, 2018)
The purpose of this research is to know the influence of vibration that occur on a machine on its power consumption along with knowing the damage that made the machine vibrated.This research conducted at PT Newmont Nusa Tenggara on Concentrator Area. Sampling pump rougher scavenger machine is used as an experiment devices. Microlog CMVA55 with accelerometer sensor was used for measuring vibration velocity and data logger was used for power consumption measurer. The vibration velocity value was taken on five point in sampling pump rougher scavenger machine and the power consumption value was taken in electrical power room. Both of the measuring result will be compared to find the influence of vibration toward machine power consumption. Fish bone analysis was used to found out the root cause of the excessive vibration on the machine. The solution of the vibration problem was found by using Failure Mode and Effect Analysis method. The results showed there isan influence toward machine power consumption by the increase of vibration velocity. For 0.06 mm/s vibration velocity excalation, the power consumption increase to 40 watt per hour. For 0.08 mm/s, power consumption increase to 80 watt per hour and the highest is 324 watt per hour with vibration velocity excalation up to 0.36 mm/s. The highest power consumption 17 kWh occurred on machine A with vibration velocity average is 6.12 mm/s and the lowest occurred on machine B that is 15 kWh with vibration velocity average is 2.99 mm/s.Keywords: vibration, vibration velocity, vibration spectrum, power consumption, mechanical vibration, spectrum analyze.